High Concentration of Glucose Increases Reactive Oxygen Species Generation and Apoptosis Induced by Endoplasmic Reticulum Stress Pathway in Rabbit Corneal Epithelial Cells - Jiajun Lu; Minjie Sheng; Panpan Yao; Chaochao Ran; Hao Liu; Li Chen; Rui Liu; Bing Li (Journal of Ophthalmology)
Objective. To investigate the effect of high concentration of glucose on reactive oxygen species (ROS) production in rabbit corneal epithelial cells (RECEs) and explore whether the increased ROS initiates the apoptosis process of RECEs through oxidative stress and endoplasmic reticulum (ER) stress pathway. Methods. RECEs were treated by different concentrations of glucose for a while, and then the production of ROS was detected by flow cytometry. The expressions of PERK, p-PERK, Akt, p-Akt, and CHOP were determined by western blot, and the cell viability was measured by Cell Counting Kit-8 (CCK-8). Flow cytometry was used to detect the early apoptosis rate. Meanwhile, the effects of N-acetyl-L-cysteine (NAC), an active oxygen inhibitor, on the experimental results were observed. Results. Compared with the normal glucose concentration group, the fluorescence intensity of ROS in the high concentration (1 mM glucose) of glucose group was significantly increased (P<0.05). NAC-inhibited ROS production was induced by high concentration of glucose (P<0.05).Western blot demonstrated that the expressions of the p-PERK and CHOP increased significantly (P<0.05), the p-Akt expression decreased (P<0.05), and the PERK and Akt expressions did not change significantly in the high concentration of glucose group compared to the normal concentration group. CCK-8 results revealed that compared with the normal concentration of glucose group, the cell activity of the high concentration of glucose group decreased. For the cells in the high concentration of glucose group, the cell survival rate of NAC-treated cells was higher than that of untreated (P<0.05). The flow cytometry results indicated that the early apoptosis rate of the cells in the high concentration of glucose group increased in contrast with that in the normal concentration of glucose group (P<0.05). Treating the cells in the high concentration of glucose group with NAC could reduce the cell apoptosis resulted from high glucose (P<0.05). Conclusions. High concentration of glucose may induce the formation of ROS which leads to oxidative stress and ER stress in RECEs and even leads to cell apoptosis. The reactive oxygen inhibitor, NAC, can play a protective character in the high concentration of glucose environment. These results might provide theoretical basis for the study of the diabetes-related dry eye.